2017
DOI: 10.3892/or.2017.5935
|View full text |Cite
|
Sign up to set email alerts
|

α7 nicotinic acetylcholine receptor in tumor-associated macrophages inhibits colorectal cancer metastasis through the JAK2/STAT3 signaling pathway

Abstract: Considerable evidence has implied that α7 nicotinic receptor subtypes play an important role in chronic inflammatory and neuropathic pain signaling. The aim of the present study was to determine the role of endogenous α7nAChR signaling in tumor-associated macrophages (TAMs) in human colorectal cancer (CRC) metastasis and prognosis. α7nAChR expression in primary tumor cells and adjacent stroma cells especially in TAMs in 51 CRC patients was observed. Using a human monocyte THP-derived macrophages (TMs) with α7n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In the brain, activation of α7nAChR in macrophages inhibits production of inflammatory cytokines (63). In colorectal cancer, the activation of α7nAChR in tumor macrophages inhibits colorectal cancer metastasis through the JAK2/STAT3 signaling pathway (64). α7nAChR has been considered an important drug target for the inhibition of lung cancer (65).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, activation of α7nAChR in macrophages inhibits production of inflammatory cytokines (63). In colorectal cancer, the activation of α7nAChR in tumor macrophages inhibits colorectal cancer metastasis through the JAK2/STAT3 signaling pathway (64). α7nAChR has been considered an important drug target for the inhibition of lung cancer (65).…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 (signal transducer and activator of transcription 3) promotes multiple signaling pathways involving the mediation of cell proliferation, invasion, epithelial‐mesenchymal transition (EMT) and angiogenesis and has been considered as a key target for cancer therapy . Increasing evidence has shown the existence of genetic variation and amplification of STAT3 in major malignancies . STAT3 signaling pathway plays a vital role in cancer progression and tumor microenvironment, indicating that it may be used as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Increasing evidence has shown the existence of genetic variation and amplification of STAT3 in major malignancies. [19][20][21][22] STAT3 signaling pathway plays a vital role in cancer progression and tumor microenvironment, 23,24 indicating that it may be used as a therapeutic target.…”
mentioning
confidence: 99%
“…Infiltration of macrophages in the tumor stroma are negative prognostic factors in COAD (Waniczek et al, 2017). It has been confirmed that the α7 nicotinic acetylcholine receptor of tumor-associated macrophages could inhibit the metastasis of COAD through the JAK2/STAT3 signaling pathway (Fei et al, 2017). What's more, macrophages are critical factors in the process of liver metastasis of COAD (Zhou et al, 2010;Imano et al, 2011;Cui et al, 2013;Kee et al, 2014).…”
Section: Discussionmentioning
confidence: 91%